2004
DOI: 10.1007/s00775-004-0618-0
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of the biomimetic [Cr3O(O2CCH2CH3)6(H2O)3]+ increases insulin sensitivity and improves blood plasma variables in healthy and type 2 diabetic rats

Abstract: The in vivo effects of gavage administration of the synthetic, functional biomimetic cation [Cr(3)O(O(2)CCH(2)CH(3))(6)(H(2)O)(3)](+) to healthy and type 2 diabetic model rats are described. After 24 weeks of treatment (0-1,000 microg Cr/kg body mass) of healthy Sprague Dawley rats, the cation results in a lowering (P < 0.05) of fasting blood plasma low-density lipoprotein (LDL) cholesterol, total cholesterol, triglycerides, and insulin levels and of 2-h plasma insulin and glucose concentrations after a glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
1
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 57 publications
7
44
1
4
Order By: Relevance
“…The dose of chromium niacinate or chromium picolinate used in this study is 400 µg Cr 3+ /kg body weight of rat. This chromium dose used in the present study is similar to that has been previously used by other investigators in chromium supplementation studies with diabetic rats or mice (25,28,34). Thus, Cr 3+ supplementation dose used per body weight in the present rat study is much higher than that has been used in human clinical trials.…”
Section: Discussionsupporting
confidence: 61%
“…The dose of chromium niacinate or chromium picolinate used in this study is 400 µg Cr 3+ /kg body weight of rat. This chromium dose used in the present study is similar to that has been previously used by other investigators in chromium supplementation studies with diabetic rats or mice (25,28,34). Thus, Cr 3+ supplementation dose used per body weight in the present rat study is much higher than that has been used in human clinical trials.…”
Section: Discussionsupporting
confidence: 61%
“…Previous studies (17,22,23) have demonstrated that treatment with chromium may reduce serum lipid levels in diabetic conditions. However, the present study fails to confirm any lipid-lowering effect from chromium treatment in obese mice.…”
Section: Discussionmentioning
confidence: 99%
“…Wzrost stężenia tej frakcji stwierdzono u szczurów otyłych z insulinoopornością lub cukrzycą, które otrzymywały pikolinian lub nikotynian chromu (49). Dodanie natomiast do diety zwierząt biomimetycznego kompleksu chromu spowodowało obniżenie stężenia cholesterolu HDL w osoczu (23,58,98). Poziom glukozy (1, 104) oraz GTF (87) Jeżeli chodzi o cechy tuczu, to wielu badaczy zwró-ciło na nie szczególną uwagę.…”
Section: Chrom W Badaniach Na Zwierzętach I Ludziachunclassified
“…Cr w formie organicznej jest lepiej wchłaniany niż w formie nieorganicznej i prowadzi do wzrostu koncentracji tego składnika w tkankach (80). Zauważono, że biodostępność kationu propionianu chromu (CrProp) jest znacznie wyższa w porównaniu do innych popularnych suplementów chromu w diecie, takich jak: chlorek, nikotynian lub pikolinian chromu (23,94,95). CrProp jest absorbowany z dużą skutecznością 40-60% (94,95).…”
Section: Toksykokinetykaunclassified